Political efficacy and political participation as influenced by the kind of work setting of organizations and socio-economic profile of employees a case study on employees working in Centralize and decentralize work settings. - Cadelina, Angelita L.
Political efficay and political participation are considered as essential conditions for democracy to thrive and are signs of political health. Many studies on the dynamics of these two concepts in order to know the factors on which these two are dependent on. This study attempts to look on several factors that affect an individuals' political efficacy and political participation., Some of the variables of socio-economic profile such as age, gender, civil status, and educational attainment were considered in this study as factors that maybe significant to an individuals' political efficacy and political participation. Results of previous studies showed that the higher the socio-economic status, the higher is one's level of political efficacy and political participation. Another factor considered in this study was the work setting of individuals, namely, the centralized work environment. Pateman (1970) and colleagues argued that democratized industrial authority structures require workers to develop skills and resources necessary for participation in political life beyond the workplace while centralized organizations socializes employees to passivity and political apathy. With these two different conditions, they claimed that employees within decentralized organizations are more likely to have a higher level of political efficacy and political participation compared to those in centralized work settings. However, results of this study showed that the profile of the respondents does not have any relationship on their level of political efficacy and political participation. Only age and political efficacy are correlated. In addition, the result was not consistent with the argument of Pateman. The result of the study showed that respondent employees from centralized and decentralized organization both have relatively medium-high level of political efficacy and political participation. This simply shows that despite the autocratic structure of decision-making, there are still some instances present in centralized organizations that could alos provide some venues for employees to increase their feeling of personal confidence and efficacy which can consequently influence their level of political efficacy and political participation.